Effect of Point Defect in Carbon Nanotube (8.0) on the Molecular Electrostatic Potential distribution Near it Edge - Datsyuk, A.M. (Physics and Chemistry of Solid State, 2015)
The influence of point defect on the electronic and spatial structure of carbon nanotubes (8.0) have been studied depending on the placement vacancies in the structure of nanotubes. On the basis of quantum-chemical calculations and using semi-empirical and ab initio approaches the maps of the distribution of molecular electrostatic potential were builds in the planes which are perpendicular to the main axis of the nanotubes. It is shown that defects such as vacancy, are placed outside the first hexagonal carbon belt no effect on the topology of the distribution of molecular electrostatic potential in the vicinity of the entrance to the carbon nanotube. Instead, reactivity of port’s atoms such nanotubes may determinated point defects of the vacancy type to be placed in first hexagonal belt.